Exploring barriers to accessing treatment for Lymphatic Filariasis through a socio-ecological lens in Buvuma and Napak districts, Uganda. - Arthur Bagonza; Linda Gibson; Lydia Kabiri; Chris Bezalel; Saravu Rama Bhat Narahari; Peter J Franks; David Musoke; Christine Moffatt (PLoS Neglected Tropical Diseases)
Background The World Health Organization launched the Global Programme to Eliminate Lymphatic Filariasis in 2000, which aimed at eradicating the disease by 2030. This goal depends on community mass drug administration and essential care. Despite these efforts, many rural communities still face untreated lymphatic filariasis and lack access to treatment and self-management. Using a socioecological model, this study examined barriers to treatment and support for people living with lymphatic filariasis in Uganda's Buvuma and Napak districts. Methods We conducted 12 key informant interviews with health facility officials, district health officers, and village health team members. Additionally, 19 focus group discussions were held with community members, and nine in-depth interviews were conducted with people living with lymphatic filariasis. This study explored knowledge gaps among those living with lymphatic filariasis and health providers that affect morbidity management and disability prevention, as well as challenges in accessing treatment. Audio recordings were transcribed and managed via ATLAS ti software version 6. Thematic analysis was conducted via the socioecological model framework. Results This study identified multiple complex factors affecting healthcare providers and individuals living with lymphatic filariasis, spanning individual, interpersonal, organisational, community, and policy levels. The key themes included stigma and social isolation, healthcare disparities, and healthcare dynamics. Stigma and social isolation result in emotional distress, neglect, exclusion, and self-isolation, which are influenced by community beliefs. Health systems and policy barriers included poverty, inadequate personnel, and insufficient equipment. Structural factors such as geographical remoteness, environmental harshness, and lack of healthcare infrastructure were prominent obstacles to seeking care for lymphatic filariasis management. Conclusion This study provides insights into the multilevel factors influencing the understanding and availability of treatment for lymphatic filariasis in Uganda. Addressing sociocultural beliefs, social and interpersonal dynamics, and healthcare disparities is crucial for improving the outcomes and well-being of these rural communities. These findings can aid in managing lymphatic filariasis in Uganda and similar low-resource settings.